Collaborative Governance in the Development of Kassi Tourism Villagein Rumbia District, Jeneponto Regency - Nasta, Asyifah; Andi Aslinda; Andi Cudai Nur; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2025)
This study aims to analyze Collaborative Governance in the development of Kassi Tourism Village in Rumbia District, Jeneponto Regency, as well as the determinant factors that influence this collaborative governance. Specifically, the research focuses on identifying both supporting and inhibiting factors that affect the development of Kassi Tourism Village. Employing a qualitative approach with descriptive methods, data were collected through a combination of observation, interviews, and documentation techniques to gain a comprehensive understanding of the governance dynamics at play. The data analysis technique utilized in this research is interactive data analysis, which involves several stages, including data condensation, data presentation, and conclusion drawing. The results indicate that Collaborative Governance in the development of Kassi Tourism Village has not been implemented optimally. Among the five indicators analyzed based on Ansell and Gash's theory, two indicators—1) Face-to-Face Dialogue and 3) Commitment to the Process—are still poorly implemented. In contrast, the other three indicators—2) Trust Building, 4) Sharing Understanding, and 5) Intermediate Outcomes—have been effectively executed. Notably, trust building emerges as the most dominant indicator in the collaboration process, as it fosters a sense of security that encourages stakeholders to take risks in collaborative efforts. However, the dominance of these positive indicators is insufficient to achieve optimal collaboration. The determinant factors influencing Collaborative Governance in the development of Kassi Tourism Village include several supporting factors, such as the diversity of tourism potential, the collaborative roles of internal parties, and the commitment of the private sector. Conversely, the inhibiting factors encompass limited human resources in the tourism sector, a lack of collaboration with local governments, and uneven infrastructure and tourism facilities. Addressing these challenges is crucial for enhancing collaborative governance and ensuring the sustainable development of Kassi Tourism Village, ultimately contributing to the economic growth and cultural preservation of the region.